USING SOFTWARE COMPLEXES IN TEACHING MATHEMATICAL ANALYSIS (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
This article explains one of the basic concepts of the course of mathematical analysis about the possibilities of calculating the concept of limit from programming packages through Maple.It is well known that no matter what sphere of life of society, its tasks, projects and industries cannot be implemented without complex mathematical calculations.  To facilitate such calculations, many powerful and universally integrated systems, i.e., application packages, have been created.  An application package is a collection of related applications that solve problems in a particular area.  This definition of an application package covers a wide range of software developments designed to enhance the usability of computers through the combined use of application and system software.